Cover Feature: High‐Voltage Nickel‐Rich NMC Cathode Material with Ionic‐Liquid‐Based Polymer Electrolytes for Rechargeable Lithium‐Metal Batteries (ChemElectroChem 17/2020). Issue 17 (12th August 2020) - Gupta, Himani; Singh, Rajendra Kumar
Abstract : The Cover Feature shows that when a nickel–manganese–cobalt (NMC) based cathode is charged at a high cut‐off voltage, an excess number of Li + ions is extracted from the layers of the NMC cathode material. It results in electrostatic repulsion between the oxygen layers and provides a higher capacity and energy density for the Li battery. In addition to the environmentally friendly and safe nature of the ionic liquid, its incorporation into polymer electrolytes provides a conducting, flexible and mechanically stable polymer electrolyte, which helps in improving the cyclic stability of the battery. More information can be found in the Article by H. Gupta and R. K. Singh .